2020
DOI: 10.1039/c9bm02010a
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of indocyanine green dye in polymeric micelles for NIR-II fluorescence imaging and cancer treatment

Abstract: Encapsulation of ICG and IR-1061 in PCL–PEG micelles producing agents with increased stability of ICG and tunable PTT and PDT activity. The micelles are also useful for NIR imaging and NIR nanothermometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…In addition, several other fluorescent compounds even suggest their potentials as novel anti-CSC agents [19,20]. For these fluorescent dyes, simultaneous cancer targeting, imaging, and cancer killing are a major advantage for cancer biology research and are expected to contribute to the future cancer therapy directions including photodynamic therapy (PDT) [21][22][23]. Furthermore, several specific membrane molecules targeting cancer cells have already been used in the in vivo NIR photoimmunotherapy field [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several other fluorescent compounds even suggest their potentials as novel anti-CSC agents [19,20]. For these fluorescent dyes, simultaneous cancer targeting, imaging, and cancer killing are a major advantage for cancer biology research and are expected to contribute to the future cancer therapy directions including photodynamic therapy (PDT) [21][22][23]. Furthermore, several specific membrane molecules targeting cancer cells have already been used in the in vivo NIR photoimmunotherapy field [24].…”
Section: Introductionmentioning
confidence: 99%
“…As emphasized in Table 1 , is used as a counter anion in IR-1040, IR-1048, and IR-1061 ( Figure 1 c,d). Among them, IR-1061 has been embedded in a variety of nanostructures such as polymeric micelles and solid nanoparticles and used for biophotonic applications [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Thinking about why such heavy anions are coordinated with the NIR organic dyes gives a hint on selecting proper surroundings in organic/inorganic hybrid nanostructures.…”
Section: Design Basics Of Near Infrared Fluorescent Nanostructurementioning
confidence: 99%
“…NIR imaging of tumors in mice using affibody functionalized CH1055 was also conducted [40]. More recently, our group and several others found that a commercially available dye, indocyanine green (ICG), the only NIR dyes that are approved by the Food and Drug Administration (FDA) for clinical use in humans, with an emission peak of 830 nm can be used to NIR fluorescence imaging in the second NIR window [41].…”
Section: Nir Molecular Probesmentioning
confidence: 99%